EFEKTIVITAS MODEL DISCOVERY LEARNING BERBANTUAN MEDIA EDUCAPLAY TERHADAP KEMANDIRIAN BELAJAR SISWA PADA MATERI AKU DAN LINGKUNGAN SEKITARKU KELAS V SDN BOJONG RAWALUMBU XI - Amalia, Zafirah Nur; Catur Putri, Fara Diba (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low level of student learning independence. This is indicated by low initiative in the learning process. Furthermore, the learning process is still teacher-centered, resulting in students tending to be passive and lacking opportunities to develop their learning independence. The purpose of this study was to determine the effectiveness of the discovery learning model assisted by Educaplay media on students' learning independence. This was an experimental study with a quantitative approach. Sampling was conducted using a purposive sampling technique. To obtain data, the researcher conducted a pre-test and a post-test. The results showed a significant difference between the learning independence of students who used the discovery learning model assisted by Educaplay media and those who did not. Based on the results of the hypothesis test using the Independent Samples I-Test using SPSS version 26 for Windows, a significance value (Sig. 2-tailed) of 0.000 < 0.05 was obtained, thus rejecting Ho and accepting Hi. Therefore, it can be concluded that the implementation of the discovery learning model assisted by Educaplay media is significantly effective in improving student learning independence.